Linguistic Interpretation Of The Concept Of Ergonym - Zokir kizi, Omonkulova Mokhinur (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
Ergonyms are interpreted as the names of institutions or associations established and operated by people. This area of onomastics serves as the foundation for a number of promising studies in linguistics. This article discusses the linguistic analysis and lexical-semantic structure of ergonyms.